2014
DOI: 10.1080/14703297.2014.910128
|View full text |Cite
|
Sign up to set email alerts
|

The student voice in higher education curriculum design: is there value in listening?

Abstract: This article presents a case study illustrating the potential value of enhanced student participation in higher education (HE) curriculum development, in response to an absence of research in this area. Lecturers and students had divergent views of the effectiveness of a staff-led redesign of a module curriculum. Focus groups were used to investigate reasons for the opposing views informing a second, more successful, redesign evidenced by improved feedback, attendance and marks. We discuss how a closer alignme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(97 citation statements)
references
References 22 publications
(31 reference statements)
3
93
0
1
Order By: Relevance
“…Seeing the issues through the eyes of students tended to focus our suggestions for practice on how to transfer well-established pedagogic suggestions (O'Donovan, Rust and Price, 2015) into practice, via modular and course-level strategies, rather than individual pieces of work. This confirms the findings of previous studies that the value of the student voice in curriculum development may be to provide a valuable lens through which to implement pedagogic knowledge (Brooman, Darwent and Pimor, 2015).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Seeing the issues through the eyes of students tended to focus our suggestions for practice on how to transfer well-established pedagogic suggestions (O'Donovan, Rust and Price, 2015) into practice, via modular and course-level strategies, rather than individual pieces of work. This confirms the findings of previous studies that the value of the student voice in curriculum development may be to provide a valuable lens through which to implement pedagogic knowledge (Brooman, Darwent and Pimor, 2015).…”
Section: Discussionsupporting
confidence: 80%
“…The value of enhanced student involvement in curriculum development by way of enhanced dialogue, which may fall short of full partnership, shown in previous studies is also supported (Brooman et al, 2015). Although the personal impact of involvement in this process is limited to these particular students, their contributions may help future students if the new suggestions are implemented and followed up by course teams.…”
Section: Discussionmentioning
confidence: 64%
“…There is some evidence, for example, that the professional requirements of some degrees leads some staff to question the potential involvement of students in designing curricula. In a study in a law school in the UK, Brooman, Darwent, and Pimor (2015) found that although staff were concerned about the need to maintain control due to the external body requirements, staff-student collaboration enhanced teaching and learning practice. Seale (2009) suggests that this new area of participation has the power to both empower students and increase the possibility that staff will respond to student voices.…”
Section: Staff Perspectives Of Collaborationmentioning
confidence: 99%
“…However, as described by Brooman, the team did not escalate the amount of material and instead favored more discussions to achieve better basic understanding. (Brooman et al, 2015) …”
Section: Institutional Supportmentioning
confidence: 99%